THE INFLUENCE OF VIDEO ADVERTISING, PRICE DISCOUNTS AND FREE TIKTOK SHOP SHIPPING ON PURCHASE INTEREST OF NORTH SUMATRA UNIVERSITY STUDENTS - Tursina, Zahra; Adlina, Hafiza (Transpublika Publisher, 2024)
Tiktok Shop is an e-commerce platform highly sought after by Indonesian consumers, with a significant presence in the global market. This research seeks to evaluate the impact of video advertising, discounts, and free shipping on purchasing intent among students at the University of North Sumatra. Employing a quantitative methodology, this study utilized a sample of 100 students who are TikTok users. The sampling technique employed was purposive sampling, with 100 respondents participating. Primary data was collected through questionnaires distributed via Google Form, complemented by secondary data from existing literature. The research involved testing the reliability and validity of the research instrument, assessing classical assumptions, and analyzing hypotheses through multiple linear regression in SPSS. The findings demonstrate that video advertising, discounts, and free shipping exert a significant and positive influence on the purchasing intent of University of North Sumatra students, both individually and collectively. The results of the F-test indicate that the three independent variables jointly account for a substantial 47% influence on the purchasing intent of University of North Sumatra students.